Disaster Planning Tips for Older Adults - Carolyn S. Wilken; Linda B. Bobroff; Emily Minton (EDIS, 2011)
Disaster can strike without warning. An important part of planning for a disaster is to have a plan for what you will do if you have to leave your home. Pick a place to meet family members or a close friend in the event that you have to evacuate. Communications often are down early in a disaster, so knowing where to meet loved ones or friends ahead of time is helpful. Use the special tips in this 4-page revised fact sheet to plan and prepare for any emergency. Written by Carolyn S. Wilken, Linda B. Bobroff, and Emily Minton and published by the UF Department of Family Youth and Community Sciences, February 2011.